Poly[diaquatetra-μ-selenocyanato-cadmium(II)dipotassium(I)] - Reinert, Thorben (International Union of Crystallography, 2010)
In the title compound, [CdK(2)(NCSe)(4)(H(2)O)(2)](n), the cadmium(II) cation is situated on a twofold rotation axis and is coordinated in a slightly distorted tetrahedral geometry by two symmetry-related μ-1,1,1,3 and two-symmetry related μ-1,1,3,3 bridging selenocyanate anions, all of which are Se bonded. These bridging selenocyanate anions are further coordinated to two symmetry-related potassium ions. Each of the potassium ions is coordinated by one terminally bonded water molecule and six selenocyanate anions, two of which are crystallographically independent. The asymmetric unit consists of one cadmium and one potassium cation, two bridging selenocyanate anions and one water molecule. The polymeric subunits are further connected via the selenocyanate anions into a three-dimensional coordination network. In this coordination network, intramolecular hydrogen bonds between neighbouring water molecules can be found.